Humanitarians in court: how duty of care travelled from human resources to legal liability. Issue 3 (2nd September 2018) - Sandvik, Kristin Bergtora
Abstract: This article explores the process of legalization as a shift in the way humanitarian actors are held accountable. The analysis is developed at the interface of legal sociology, legal anthropology and at the margins of an anthropology of the Norwegian welfare state. Through an account of the groundbreaking Steven Patrick Dennis v. the Norwegian Refugee Council (NRC) case litigated in Oslo District Court in 2015, I show how the evolving juridification of humanitarian organizations' duty of care for their staff is transforming both the content and the framing of the relationship between employers (NGOs) and employees (NGO workers), and perceptions of the moral duties and humanitarian worker subject positions that underpin this relationship. Over the last decade, the NRC has gone through a period of exceptional growth and has evolved to become one of the humanitarian sectors most well-known and respected actors. Despite this prominence, there is no critical academic engagement with the organization's work or its institutional culture. The article aims to bridge that knowledge gap.